Exemplary in Islamic Education to Create a Rabbani Generation - Marits, Milhatunnisa (At-Ta’dib, 2022)
Education is the key to human life and a major factor in the development of a nation. Education is how to humanize the human race. Education lasts a lifetime and can be done anywhere. There are three primary components of education: input, process and output. Islamic education focuses on teaching, educating man to accomplish the purpose of his creation of being a servant of god and the caliph of the earth. This method of writing involves the study of literature through articles, books, and other reading sources. This paper discusses how islamic education through exemplary methods could give birth to a superior generation of rabbani to the nation’s successor. The prophet Muhammad was the best paragon we could model, both for a student, teacher, and also for a parent. Teachers and parents must also understand and exemplify the prophet Muhammad so that he can also be a good example to his son. By example there will be a generation of rabbani, a generation that understands the concept of homepage, namely, the purpose, function and mission of the creation of man. Good example became an effective method of islamic education for the birth of superior generations. Â